2021
DOI: 10.1080/00016357.2021.1921842
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status in long-term orthodontic retention patients up to 10 years after treatment – a cross-sectional study

Abstract: Vandevska-Radunovic (2021): Periodontal status in long-term orthodontic retention patients up to 10 years after treatment -a cross-sectional study, Acta Odontologica Scandinavica,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…We previously demonstrated that smoking was associated with gingival bleeding evident upon clinical examination [21]. The current study also showed that patient-reported gingival bleeding was associated with smoking.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We previously demonstrated that smoking was associated with gingival bleeding evident upon clinical examination [21]. The current study also showed that patient-reported gingival bleeding was associated with smoking.…”
Section: Discussionsupporting
confidence: 76%
“…Patient demographics for the study population were previously reported by the research group (Table 1) [21]. Seventy-seven percent of the patients experienced no difficulty maintaining oral hygiene, and 13% experienced dental sensitivity (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvesen et al ( 2021) [96] concluded that prolonged fixed retention per se does not have harmful periodontal outcomes, but coexisting factors such as smoking and hand dexterity may increase the risk of plaque accumulation causing inflammation. In fact, their sample self-reported that they felt confident for effective oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…10 In general, it does not seem that the mere presence of xed retainers alone is associated with harmful effects on periodontal health, but additional predisposing factors such as the cumulative effect of age and the difference in the gender of patients (due to the difference in attention level to hygiene habits), may increase the risk of plaque deposition and pocket depth. 11 Before treatment, the orthodontist must make sure that the patient is able to perform adequate oral hygiene instructions. In patients who do not follow the necessary oral and dental hygiene tips, active orthodontic treatment should also be postponed until satisfactory plaque control is achieved.…”
Section: Introductionmentioning
confidence: 99%